Ab initio Everolimus-Based vs. Standard CNI Immunosuppression-Regimen in Liver Transplant Recipients. (July 2018) - Manzia, Tommaso Maria; Quaranta, Claudia; Toti, Luca; Sforza, Daniele; Pellicciaro, Marco; Vella, Ivan; Tariciotti, Laura; Tisone, Giuseppe
Abstract : Aim: We designed a retrospective case-control study to determine the efficacy and feasibility of everolimus (EVR) combined with low-dose tacrolimus (Tac) ab initio vs. standard-dose Tac after liver transplantation (LT). Methods: Between September 2009 and June 2015 seventy-one adult LT patients, receiving EVR and low-dose Tac without corticosteroids or induction therapy from post-operative day 1 (EVR group), were compared with a well-matched control group of 61 recipients treated with standard-dose Tac in association with antimetabolite. Results: Baseline characteristics for the two groups were comparable. The median study follow-up was 27 months (range: 0-82). The overall patient and graft survival were similar (p=0.908). Liver function was stable during the follow-up. In the EVR group, biopsy-proven acute rejection occurred in 2 cases (2.8%), while chronic rejection in one (1.4%). The EVR group experienced a better renal function already after 2 weeks [eGFR: 89.85 (36.46-115.3) ml/min/1.73m2 vs. 68.77 (16.11-115.42)ml/min/1.73m2, (p=0.013)], which was also observed after a median time of 27 (range 0-82) months from LT [eGFR: 80 (45-118.3)ml/min/1.73m2 vs. 70.9(45-88.4)ml/min/1.73m2, (p=0.04)]). After a median time of 27 months, the EVR-group showed lower incidence of arterial hypertension and insulin-dependent diabetes mellitus. Conclusion: Ab initio EVR-based immunosuppression could be a valid option immediately after surgery in recipients at high-risk of post-LT renal impairment.